Empowering Language teacher educators: the impact of training, emotions, leadership, and infrastructure on digital pedagogy and the facilitation of future teachers’ competence - Ma, Huiling; Ismail, Lilliati (Springer, 2025)
With the ongoing digital transformation in education, digital competence has emerged as a crucial 21st-century skill, necessitating that educators master digital pedagogy and support their students in developing these competencies. However, existing studies have predominantly focused on pre- and in-service language teachers. Limited research has examined how language teacher educators prepare future language teachers to develop digital competence. Moreover, most existing studies emphasize specific educator competencies while overlooking the broader contextual factors that shape these outcomes. This study adopts a holistic perspective by examining the roles of effective training, positive emotions, digital leadership, and infrastructure in enhancing language teacher educators’ digital pedagogy and their ability to foster digital competence among future language teachers. A total of 239 language teacher educators from six institutions participated in this study, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The study found that effective training and digital pedagogy significantly enhance language teacher educators’ ability to facilitate student digital competence, while digital infrastructure positively influences effective both training and positive emotions. However, digital leadership and infrastructure did not directly impact digital pedagogy or student facilitation, highlighting the need for more integrated approaches to digital education. This research offers valuable insights for policymakers and institutional leaders aiming to strengthen digital teaching practices in language teacher education.